2015
DOI: 10.1051/0004-6361/201526219
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation signatures in the Flora region

Abstract: Context. Most asteroid families are very homogeneous in physical properties. Some show greater diversity, however. The Flora family is the most intriguing of them. The Flora family is spread widely in the inner main belt, has a rich collisional history, and is one of the most taxonomically diverse regions in the main belt. As a result of its proximity to the asteroid (4) Vesta (the only currently known intact differentiated asteroid) and its family, migration between the two regions is possible. This dynamical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
2
16
0
Order By: Relevance
“…Generally the inner main belt is considered to be the main source region of meteorites. Oszkiewicz et al (2015) and Oszkiewicz et al (2017) show that some V-type prograde rotators in the inner main belt have Yarkovsky drift direction that is inconsistent with origin in the Vesta family and may represent parent bodies of those anomalous HEDs. Spectroscopic surveys of this region (Burbine et al 2001;Moskovitz et al 2010;Mayne et al 2011) have yet to unambiguously identify V-type asteroids that are not related to Vesta.…”
Section: Introductionmentioning
confidence: 99%
“…Generally the inner main belt is considered to be the main source region of meteorites. Oszkiewicz et al (2015) and Oszkiewicz et al (2017) show that some V-type prograde rotators in the inner main belt have Yarkovsky drift direction that is inconsistent with origin in the Vesta family and may represent parent bodies of those anomalous HEDs. Spectroscopic surveys of this region (Burbine et al 2001;Moskovitz et al 2010;Mayne et al 2011) have yet to unambiguously identify V-type asteroids that are not related to Vesta.…”
Section: Introductionmentioning
confidence: 99%
“…Here we will thus mention only a few more recent papers, including e.g. Nesvorný et al (2015), and Bolin et al (2017), who claim that they identified the family, while Oszkiewicz et al (2015) and Erasmus et al (2019) warn of a significant diversity in the taxonomy of asteroids in the region. Apart from Flora "family", only two more families are found in Zone 2: a somewhat dubious (see e.g.…”
Section: Zonementioning
confidence: 99%
“…Asteroid families, created by collisions, are a unique tool to study both the internal structure of their parent body, and the surface and dynamical evolution of their member, hence of the asteroid belt (DeMeo et al 2019;Spoto et al 2015;Oszkiewicz et al 2015). The Asteroids-Dynamic Site 9 (AstDyS-2) provides catalogues of the proper elements of the asteroids as well as of asteroid families and family membership obtained from the analysis of proper elements (see Milani et al 2014).…”
Section: Asteroid Familiesmentioning
confidence: 99%